Prospective associations between televiewing at toddlerhood and later self-reported social impairment at middle school in a Canadian longitudinal cohort born in 1997/1998. Issue 16 (13th September 2016) - Pagani, L. S.; Lévesque-Seck, F.; Fitzpatrick, C.
Abstract : Background: Using a large Canadian population-based sample, this study aimed to verify whether televiewing in toddlerhood is prospectively associated with self-reported social impairment in middle school. Method: Participants are from a prospective–longitudinal birth cohort of 991 girls and 1006 boys from the Quebec Longitudinal Study of Child Development. Child self-reported ratings of relational difficulties at age 13 years were linearly regressed on parent-reported televiewing at age 2 years while adjusting for potential confounders. Results: Every additional 1 h of early childhood television exposure corresponded to an 11%s.d. unit increase in self-reported peer victimization [unstandardized β = 0.03, 95% confidence interval (CI) 0.02–0.04], a 10%s.d. unit increase in self-reported social isolation (unstandardized β = 0.04, 95% CI 0.03–0.05), a 9%s.d. unit increase in self-reported proactive aggression (unstandardized β = 0.02, 95% CI 0.01–0.03) and a 6%s.d. unit increase in self-reported antisocial behavior (unstandardized β = 0.01, 95% CI 0.01–0.01) at age 13 years. These results are above and beyond pre-existing individual and family factors. Conclusions: Televiewing in toddlerhood was prospectively associated with experiencing victimization and social withdrawal from fellow students and engaging in antisocial behavior and proactive aggression toward fellow students at age 13 years. Adolescents who experience relational difficulties are at risk of long-term health problems (like depression and cardiometabolic disease) and socio-economic problems (like underachievement and unemployment). These relationships, observed more than a decade later, and independent of key potential confounders, suggest a need for better parental awareness of how young children invest their limited waking hours.